Pro SQL Server 2022 wait statistics : a practical guide to analyzing performance in SQL Server and Azure SQL Database - LaRock, Thomas; Laar, Enrico van de (ITpro collection, 2023)
Use this practical guide to analyze and troubleshoot SQL Server performance using wait statistics. You'll learn to identify precisely why your queries are running slowly. And you'll know how to measure the amount of time consumed by each bottleneck so you can focus attention on making the largest improvements first. This edition is updated to cover analysis of wait statistics current with SQL Server 2022. Whether you are new to wait statistics, or already familiar with them, this book provides a deeper understanding on how wait statistics are generated and what they mean for your SQL Server instance’s performance. The book goes beyond the most common wait types into the more complex and performance-threatening wait types. You’ll learn about per-query wait statistics and session-based wait statistics, and the types of problems they can help you solve. The different wait types are categorized by their area of impact, including CPU, IO, Latching, Locking, and many more. Clear examples are included to help you gain practical knowledge of why and how specific wait times increase or decrease, how they impact your SQL Server’s performance, and what you can do to improve performance. After reading this book, you won’t want to be without the valuable information that wait statistics provide regarding where you should be spending your limited tuning time to maximize performance and value to your business.